Kematangan Beragama Jalaluddin Rumi Ditinjau Dari Prespektif W. James - Ilhami, Hablun (YASIN, 2021)
As a Sufi as well as the greatest poet in Islamic history, Jalaluddin Rumi has many things to study, starting from religious mode to his works that have become a conversation in the scientific treasures of both West and East. This is inseparable from the message that Rumi wants to covey that seem to flow in his verses. This type of research is library research, namely research that collects data through literature, be it books, articles, magazines and so on. The approach used in this research is a philosophical approach, namely the approach taken to systematically reason and organize certain data. The nature of this research is descriptive, namely the systematic decomposition of the data obtained which is then given an explanation and understanding so that it can be understood by the reader. The results of this study indicate that Jalaluddin Rumi has or is at the level of religious maturity. This can be seen from his poems which reflect Rumi’s thoughts and personality starting from closeness to God, love and so on.